Analysis and Solutions of Arcing Problem in Urban Rail Transit Vehicle Bases - LU Yumin (Chengshi guidao jiaotong yanjiu)
［Objective］ Arcing problems frequently occur in Shanghai rail transit vehicle bases, which not only damage the appearance and structure of the rails and wheels, but also affect train operation safety. Therefore, it is necessary to analyze arcing problems in the vehicle base, identify the cause of arcing, and then propose solutions. ［Method］ In the case of catenary power outage in the vehicle base, before and after disconnecting the unidirectional conduction devices on the entrance/exit lines, and when the mainline train enters and exits the station near the vehicle base, by detecting the current between the maintenance platform railing and the car body, and the current passing through the unidirectional conduction devices on the entrance/exit lines, causes for the parking garage maintenance platform railing arcing are deeply analyzed. After adjusting the exiting line power supply mode, when there is no train leaving the depot and the outbound car is driving to the main line via the exit line, the voltage at both ends of the insulating joint, the voltage of the mainline rail to the ground, and the voltage of the yard rail to the ground are measured respectively, and causes for the insulation joint arcing when the wheel passing through the entrance/exit lines are deeply analyzed. Solutions are proposed for the cause of arcing. The application effect of using an intelligent conduction device instead of the unidirectional conduction device is emphatically verified. ［Result & Conclusion］ Arcing in the maintenance platform railing is caused by the stray current leaking from the mainline rail to the parking lot. Arcing in the base entrance/exit lines insulation joint is caused by the increase of rail return current and the increase of insulation joint pressure difference due to poor current return. In addition, since the arc extinguishing device thyristor in the unidirectional conduction device is affected by the minimum holding current, the turn-on voltage and other characteristics, both insulation joint ends cannot achieve the effect of metallic electrical connection, thus resulting in unsatisfactory arc extinguishing effect. The actual application effect shows that the intelligent conduction device can effectively block the stray current path, inhibit the stray current from flowing into the vehicle base, ensure the smooth return flow, thereby reducing the arcing occurrence in the vehicle base.